Synthesis and Antifungal Activity of β-Hydroxysulfides of 1,3-Dioxepane Series - Roman S. Pavelyev; Rusalia M. Vafina; Konstantin V. Balakin; Oleg I. Gnezdilov; Aleksey B. Dobrynin; Olga A. Lodochnikova; Rashid Z. Musin; Galina A. Chmutova; Svetlana A. Lisovskaya; Liliya E. Nikitina (Journal of Chemistry)
Synthesis of β-hydroxysulfides of 1,3-dioxepane series and their further functionalization were performed. Chiral β-hydroxysulfides were separated into enantiomers using enzymatic acylation by lipase PS. Study of antifungal activity of the obtained compounds showed that some enantiomerically pure 6-arylthio-1,3-dioxepan-5-ols represent promising antifungal drug candidates.